2017
DOI: 10.3748/wjg.v23.i42.7505
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal epithelium, intraepithelial lymphocytes and the gut microbiota - Key players in the pathogenesis of celiac disease

Abstract: Celiac disease (CD) is a chronic immune-mediated disorder triggered by the ingestion of gluten in genetically predisposed individuals. Before activating the immune system, gluten peptides are transferred by the epithelial barrier to the mucosal lamina propria, where they are deamidated by intestinal tissue transglutaminase 2. As a result, they strongly bind to human leucocyte antigens (HLAs), especially HLA-DQ2 and HLA-DQ8, expressed on antigen-presenting cells. This induces an inflammatory response, which res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 124 publications
(132 reference statements)
1
73
0
1
Order By: Relevance
“…39 Increased intestinal permeability via exposure to gliadin or certain gut microbiota has been linked to the pathogenesis of CD and may account for the rates of AGA positivity in this study and warrants further investigation. 40 The use of immunoassays alone for diagnosis has been recommended for resource-poor settings where duodenal biopsy is not available. 9 However, the low positive predictive value of celiac antibodies in this study highlights the short-coming of this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…39 Increased intestinal permeability via exposure to gliadin or certain gut microbiota has been linked to the pathogenesis of CD and may account for the rates of AGA positivity in this study and warrants further investigation. 40 The use of immunoassays alone for diagnosis has been recommended for resource-poor settings where duodenal biopsy is not available. 9 However, the low positive predictive value of celiac antibodies in this study highlights the short-coming of this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in the gut microbiome may affect intestinal integrity and increase gut permeability leading to local and systemic immune response . Intestinal barrier disruption, along with genetic background and environmental factors, has been recently considered as a pivotal element in the pathogenesis of chronic inflammatory diseases, including inflammatory bowel disease and celiac disease . Recent experimental and clinical studies revealed disturbance in the balance of beneficial and pathogenic bacteria in the gut of patients with psoriasis and psoriatic arthritis .…”
Section: Introductionmentioning
confidence: 99%
“…3 Intestinal barrier disruption, along with genetic background and environmental factors, has been recently considered as a pivotal element in the pathogenesis of chronic inflammatory diseases, including inflammatory bowel disease and celiac disease. 4,5 Recent experimental and clinical studies revealed disturbance in the balance of beneficial and pathogenic bacteria in the gut of patients with psoriasis and psoriatic arthritis. [6][7][8] However, it remains unclear whether alteration in the gut microbiome and inflammatory processes in psoriasis influence the intestinal barrier.…”
Section: Introductionmentioning
confidence: 99%
“…27 Inflammation, subsequent to an impaired intestinal barrier, composition. 29,30 We speculated that the maternal inflammation caused by alteration of intestinal flora could mislead changes in nutrient supply, oxygen, and alterations in the secretion of hormones and other signaling molecules in the fetal circulation. 28 An imbalance in the gut microbiota may produce lactate or butyrate, which could regulate gut permeability and induce the gut inflammatory, lipopolysaccaharides infiltration, oxidative stress, macrophage infiltration, and consequently chronic low grade inflammation.…”
Section: Discussionmentioning
confidence: 99%